IMPROVEMENT OF KNOWLEDGE, ATTITUDE AND MATERNAL SKILLS IN NEWBORN CARE THROUGH EARLY HEALTH PROMOTION IN MATERNITY CLINIC - Siti Sa'idah Nasution; Erniyati (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2018)
Newborn period is not pleasant for the beginning, because the previous life environment in theintrauterine very different situation with after birth environment or extrauterine . The birth of eachbaby will experience the process of adaptation or adjustment of the vital functions and systems ofthe body. Proper care of newborns and in accordance with the rules of health will help the baby toadapt optimally in health. The behavior of the community, especially mothers and families stillmany who have not been in accordance with the health rules in baby care. The treatment is donetends health risk that can increase morbidity and infant mortality. Behavior consisting ofknowledge, attitudes and skills of the mother is crucial in improving the health status of the babysince birth. The provision of counseling by health workers in the community, especially at thematernity clinic in pregnant women is the first step in optimizing maternal behavior in baby care.Nursing interventions that become the focus in the care of the baby is a baby observation, care ingeneral, exclusive breastfeeding, keeping the warmth, umbilical cord care, skin care, baby bath,baby clothes and immunization.